Digital Literacy and Hate Speech under the Guise of Social Media Liberalism (Oratio Directa, 2022)
This article examines the relationship between freedom of expression, hate speech, disinformation, and digital literacy on social media. It uses a qualitative descriptive literature and document review, supported by two Indonesian cases reported in 2017 as illustrations. The analysis distinguishes liberalism from unrestricted expression: individual liberty operates together with responsibility, the rights and reputation of others, and legitimate public-order safeguards. Hate speech is discussed as expression that promotes hostility or discrimination based on group identity, while hoaxes can intensify polarization when political or religious symbols are used to manufacture credibility. The legal instruments cited are positioned as the framework referenced by the 2022 source rather than a statement of current law. The article argues that enforcement alone is insufficient. Digital literacy should combine technical access with the ability to verify sources, interpret context, recognize manipulative framing, communicate ethically, and participate without provocation or defamation. Because the source does not provide a systematic corpus or comparative data, its conclusions are conceptual and cannot establish prevalence or causal effects.
Keywords: Digital literacy; Hate speech; Freedom of expression; Social media; Disinformation